Primigravida Dengan Hiperemesis Gravidarum - Febi Susanto; Fonda Octarianingsih Shariff (THE JOURNAL OF Mother and Child Health Concerns, 2024)
Abstract The patient came to the Obgyn Polyclinic at Bintang Amin Hospital with G1P0A0 7 weeks pregnant with complaints of vomiting more than 10 times per day accompanied by nausea, weakness and sometimes dizziness. But the patient said the weight increased drastically during pregnancy. First menstruation at the age of 14 years, menstruation lasted 7 days, the patient changed sanitary napkins twice a day. On physical examination, vital signs were found including blood pressure 90/80 mmHg, pulse 72x/minute, respiratory rate 20x/minute, temperature 36.7 °C, oxygen saturation 98%. The internal vaginal examination was not carried out. On hematology supporting examination, it was found that the leukocytes were increased to 11,100 ul, the hematocrit decreased by 35%. On ultrasound examination, it was found that A: Crown Rump Lengh (CRL): 1.87 cm, B: Crown Rump Lengh (CRL): 1.63 cm. The diagnosis in this case is primigravida with hyperemesis gravidarum. The treatment received by the patient was IVFD RL + 1-amp neurobion gtt 20 tpm, ondansetron inj 3x1amp, antacid syr 3x1c/oral. The prognosis for this patient is dubia ad bonam. Keywords: HEG; Pregnant; Vomiting. Pasien datang ke Poliklinik Obgyn Rumah Sakit Bintang Amin dengan G1P0A0 hamil 7 minggu dengan keluahan muntah sudah lebih dari 10 kali perhari disertai mual, lemas dan terkadang pusing. Tetapi os mengatakan berat badan meningkat secara drastis saat hamil.Haid pertama pada umur 14 tahun, haid selama 7 hari, pasien ganti pembalut sebanyak 2x sehari. Pada pemeriksaan fisik didapatkan tanda-tanda vital diantaranya tekanan darah 90/80 mmHg, denyut nadi 72 x/menit, laju pernapasan 20x/menit, suhu 36.7 °C, saturasi oksigen 98%. Pada Pemeriksaan dalam vaginal tocher tidak dilakukan. Pada pemeriksaan penunjang hematologi didapatkan peningkatan leukosit 11.100 ul, penurunan hematokrit 35 %. Pada pemeriksaan USG didapatkan A: Crown Rump Lengh (CRL): 1.87 cm, B: Crown Rump Lengh (CRL): 1.63 cm. Diagnosis pada kasus ini yaitu primigravida dengan hiperemesis gravidarum. Tatalaksana yang didapat oleh pasien yaitu IVFD RL + 1-amp neurobion gtt 20 tpm, inj ondansetron 3x1amp, antasida syr 3x1c/oral. Prognosis pada pasien ini yaitu dubia ad bonam. Kata Kunci: Hamil; HEG; muntah.